Assessment of preschool preparedness intervention package on adoption of nutrition friendly school initiative in rural Sindh, Pakistan: a pre-and post-intervention design - Samnani, Amir Ali; Nuruddin, Rozina; Petrucka, Pammla; Soofi, Sajid B.; Karmaliani, Rozina (Frontiers in Nutrition, 2024)
In 1995, the World Health Organization launched its Global School Health Initiative intending to expand this health promotion approach throughout schools globally. In this study, we aim to assess the preparedness of preschools in the adoption of intervention packages under the Nutrition Friendly School Initiative (NFSI) checklist.From three campuses of the Aga Khan School located in the Thatta and Sujawal districts of the Sindh province, Pakistan, all eligible preschool children were selected for this study. Using a pre-and post-intervention design, we assessed preschool preparedness using the NFSI checklist, knowledge of parents/caregivers regarding health and nutrition promoting behaviors, and anthropometric measurements (i.e., mid-upper arm circumference (MUAC), weight, and height) for preschool children. The NFSI checklist was manually analyzed with differential scores, while descriptive statistics were used for anthropometric and knowledge data. Continuous variables (i.e., height, weight, MUAC) were presented as means, while categorical variables (knowledge) were expressed as numbers and percentages. Paired t-tests for dependent samples were used to statistically assess mean differences in MUAC, height, weight, height-for-age Z-score, weight-for-age Z-score, weight-for-height Z-score, and changes in parental knowledge of preschool children Results: Data from 164 school children (ages 24-83 months, mean age 56.7 months) were analyzed over three months. School preparedness scores improved from 10 to 22 points (out of 26). Parental knowledge on nutrition and health increased by 7.2 points (out of 25). Children showed mean increases in MUAC (0.27 cm), weight (0.36 kg), and height (0.62 cm) (p < 0.001). Stunting and overweight/obesity rates remained the same (7.3% and 4.3%), while underweight and wasting rates dropped from 10.4% to 7.3% and 7.9% to 6.1%, respectively. The initiative effectively reduced underweight and wasting but did not impact stunting and overweight.The NFSI has greatly enhanced preschool readiness for nutrition-friendly schools. Engaging the private sector in addressing nutritional challenges has paved the way for future public-private partnerships to tackle malnutrition. The nutrition policy formulated through this initiative could serve as a blueprint for a National School Nutrition Policy.